The Significance of Interferon-γ in HIV-1 Pathogenesis, Therapy, and Prophylaxis - Roff, Shannon R.; Song, Ezra N.; Yamamoto, Janet K. (Frontiers in Immunology, 2014)
Interferon-γ (IFNγ) plays various roles in the pathogenesis of HIV/AIDS. In an HIV-1 infected individual, the production of IFNγ is detected as early as the acute phase and continually detected throughout the course of infection. Initially produced to clear the primary infection, IFNγ together with other inflammatory cytokines are involved in establishing a chronic immune activation that exacerbates clinical diseases associated with AIDS. Unlike type-1 IFNs, IFNγ has no direct antiviral activity against HIV-1 in primary cultures, as supported by the in vivo findings of IFNγ therapy in infected subjects. Results from both in vitro and ex vivo studies show that IFNγ can instead enhance HIV-1 replication and its associated diseases, and therapies aimed at decreasing its production are under consideration. On the other hand, IFNγ has been shown to enhance cytotoxic T lymphocytes and NK cell activities against HIV-1 infected cells. These activities are important in controlling HIV-1 replication in an individual and will most likely play a role in the prophylaxis of an effective vaccine against HIV-1. Additionally, IFNγ has been used in combination with HIV-1 vaccine to augment antiviral immunity. Technological advancements have focused on using IFNγ as a biological marker to analyze the type(s) of immunity generated by candidate HIV vaccines and the levels of immunity restored by anti-retroviral drug therapies or novel immunotherapies. Hence, in addition to its valuable ancillary role as a biological marker for the development of effective HIV-1 prophylactic and therapeutic strategies, IFNγ has a vital role in promoting the pathogenesis of HIV.